Solubility-pH profiles of a free base and its salt: sibutramine as a case study - Diego Lucero-Borja; Òscar Castilla; Rafel Barbas; Xavier Subirats; Clara Ràfols (International Association of Physical Chemists (IAPC), 2017)
In the present study the solubility-pH profiles of sibutramine free base and its hydrochloride salt were determined in the pH range between 2.0 and 9.5 by means of the recommended shake-flask method, and the solids collected were dried and studied by X-ray diffraction in order to elucidate their free base or salt structure. Above pHmax (or Gibbs pKa) the solid collected was always identified as free base, whatever the sibutramine species (free base or hydrochloride salt) initially solved. However, in the pH range below pHmax different solids were isolated depending on the buffers employed.